Effect of triisopropanolamine on compressive strength and hydration of steaming-cured cement-fly ash paste. (20th December 2018) - Zou, Fubing; Tan, Hongbo; He, Xingyang; Ma, Baoguo; Deng, Xiufeng; Zhang, Ting; Mei, Junpeng; Liu, Xiaohai; Qi, Huahui
Highlights: The effect of triisopropanolamine on early strength of SCHF blends under steaming-curing was studied. TIPA favors both the hydration of cement and pozzolanic reaction of FA. TIPA has a negative effect on early strength owing to its air-entraining effect. Abstract: Fly ash (FA) has been accepted as one of the most popular supplementary material in blends with cement. However, high content of FA added would result in very slow strength development at the early age, and this problem limits the use of FA in precast concrete. In this study, an attempt was made to enhance the early strength of steam-cured high content cement-fly ash paste (SCHF, 50% FA) by incorporating triisopropanolamine (TIPA), and the underlying mechanism was systematically investigated in terms of hydration products, pore structure, and ions dissolution of FA. The early hydration process was assessed with isothermal calorimetry, thermogravimetric with differential thermo-gravimetric, and scanning electron microscopy with energy dispersive spectrometer. The pore structure of hardened paste was characterized with mercury intrusion porosimetry. The solubility of FA was analyzed with inductive coupled plasma emission spectrometer, nuclear magnetic resonance, and scanning electron microscopy. The chelating ability of TIPA with Fe 3+ and Al 3+ was evaluated with the conductivity. These results show that with the dosage of TIPA less than 0.10%, the compressive strength will increase with increasing dosage of TIPA, mainly because of the acceleration of both hydration of cement and pozzolanic reaction of FA; while with the dosage more than 0.10%, the compressive strength was sharply decreased owing to its air-entraining effect to increase the harmful pores, with negative effect on mechanical performance. The reason for the accelerated pozzolanic reaction of FA is that TIPA can accelerate the dissolution of aluminum, ferric and silicate into solution to participate in hydration. The findings are expected to provide guidance on promoting the use of FA in precast concrete.